1993
DOI: 10.1144/gsl.sp.1993.071.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Analogue sandbox modelling of Miocene extensional faulting in the Outer Moray Firth

Abstract: The Palaeogene sequence of the Outer Moray Firth in the UK sector of the North Sea consists of a series of stacked submarine-fans and associated shelf deltaic deposits. The sequence was derived from the elevated Shetland Platform to the northwest. The clastic material was transported southeastwards along the axis of the Witch Ground Graben towards the basin low in the Central Graben. Towards the top of the Palaeogene submarine-fan slope deposits, there is a disturbed sequence, Oligocene in age, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Early studies have suggested that the layer-parallel displacement of these faults is accommodated by regional extension of the host succession (e.g., Higgs and McClay, 1993;Clausen et al, 1999); a hypothesis further developed by recent field studies suggesting polygonal faults form due to radial extension (Antonellini and Mollema, 2015;Petracchini et al, 2015). As outlined above, it is difficult to explain the observed uniform distribution of fault strikes in this system by unidirectional gravity-driven or tectonic extension, but could radial extension of the host succession explain the observed fault displacement?…”
Section: Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies have suggested that the layer-parallel displacement of these faults is accommodated by regional extension of the host succession (e.g., Higgs and McClay, 1993;Clausen et al, 1999); a hypothesis further developed by recent field studies suggesting polygonal faults form due to radial extension (Antonellini and Mollema, 2015;Petracchini et al, 2015). As outlined above, it is difficult to explain the observed uniform distribution of fault strikes in this system by unidirectional gravity-driven or tectonic extension, but could radial extension of the host succession explain the observed fault displacement?…”
Section: Strainmentioning
confidence: 99%
“…(1) density inversion by differential compaction between the host succession and the overlying strata (Henriet et al, 1988;Watterson et al, 2000); (2) internal layer-parallel extension of the host succession driven by gravitational sliding (Higgs and McClay, 1993;Clausen et al, 1999); (3) hydraulic fracturing due to differential compaction and overpressure build-up (Cartwright, 1994a,b); (4) syneresis (i.e., spontaneous contraction of a sediment-water gel (Dewhurst et al, 1999); (5) low coefficients of residual friction that are too low to sustain in situ stresses along the fault plane (Goulty, 2001(Goulty, , 2002(Goulty, , 2008); (6) particle dissolution during diagenesis, which induces tensile stresses of sufficient magnitude for normal faulting (Shin et al, 2008;Cartwright, 2011); and (7) yielding, which describes behavior of clays not captured by classic Mohr-Coulomb or Drucker-Prager criteria (Laurent et al, 2012). There is thus clearly a lack of consensus on the mechanism driving polygonal faulting, reflecting, at least in part, our poor understanding of their kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…This change in sedimentation could be a result of either source area rejuvenation due to uplift, or a result of increased erosion rates due to climate change. Higgs and McClay [1993] suggest a tilt of the Moray Firth region from the NW occurred late in the deposition of the lower Miocene sequence (20 -16 Ma). As a result of this tilt, the upper Miocene deposits onlap older sequences.…”
mentioning
confidence: 89%
“…Minor Miocene extensional faulting affected Oligo-Miocene sediments in the Outer Moray Firth Basin as the Paleogene slope sequence underwent a gravitational collapse caused by the uplift of the NW region. The faulting, and hence the tilting, is timed as middle Miocene [Higgs and McClay, 1993].…”
mentioning
confidence: 99%
“…Up to now, more than 50 basins have found the existence of polygonal faults. Some geologists presented different formation mechanisms, including density inversion [3,4], gravity sliding or collapse [5], episodic hydrofracturing [6], "volumetric contraction" [7], and low coefficients of friction [8].…”
Section: Introductionmentioning
confidence: 99%